After the Farm Crisis: Religiosity in the Rural United States - Wafa Hakim Orman (Institute for the Study of Labor (IZA), 2013)
The farm crisis in the United States in the 1980s had profound effects on rural, agricultural regions of the country, but almost no impact on urban and suburban areas. I use a difference-in-difference methodology and find that religiosity as measured by religious attendance increased significantly in areas impacted by the crisis for those who worked in agriculture. Chen (2010) describes increased religiosity in Indonesia following the 1998 financial crisis, and this paper demonstrates a similar response to severe financial distress in the United States. I also find evidence that this increase is not due to a lower opportunity cost of time, as those who are currently employed have higher levels of attendance than those who are not. I hypothesize that the increased religiosity results from religious institutions' ability to provide public goods, both financial and emotional, in the form of community support.
Keywords: J22; Q12; Z12; 330; farm crisis; financial distress; religious attendance; religiosity